2020
DOI: 10.3897/neobiota.55.49158
|View full text |Cite
|
Sign up to set email alerts
|

Trait differentiation between native and introduced populations of the invasive plant Sonchus oleraceus L. (Asteraceae)

Abstract: There is growing evidence that rapid adaptation to novel environments drives successful establishment and spread of invasive plant species. However, the mechanisms driving trait adaptation, such as selection pressure from novel climate niche envelopes, remain poorly tested at global scales. In this study, we investigated differences in 20 traits (relating to growth, resource acquisition, reproduction, phenology and defence) amongst 14 populations of the herbaceous plant Sonchus oleraceus L. (Asteraceae) across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…First, similar recent (Ollivier et al 2020) and classic often‐cited (Maron et al 2004) studies have provided valuable insights without maternal corrections. For example, Ollivier et al (2020) measured 20 plant traits (including germination, seed mass, seed number, plant height, and biomass) in Sonchus oleraceus in a glasshouse experiment, and then evaluated the effects of temperature and precipitation variables on each of the traits. In that study, seeds were collected over 2 yr from 14 populations in nine countries, stored in paper bags with silica gel, and then just sown directly for trait measurements.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…First, similar recent (Ollivier et al 2020) and classic often‐cited (Maron et al 2004) studies have provided valuable insights without maternal corrections. For example, Ollivier et al (2020) measured 20 plant traits (including germination, seed mass, seed number, plant height, and biomass) in Sonchus oleraceus in a glasshouse experiment, and then evaluated the effects of temperature and precipitation variables on each of the traits. In that study, seeds were collected over 2 yr from 14 populations in nine countries, stored in paper bags with silica gel, and then just sown directly for trait measurements.…”
Section: Methodsmentioning
confidence: 87%
“…Nevertheless, we are still confident in the validity of our experimental design. First, similar recent (Ollivier et al 2020) and classic often-cited (Maron et al 2004) studies have provided valuable insights without maternal corrections. For example, Ollivier et al (2020) measured 20 plant traits (including germination, seed mass, seed number, plant height, and biomass) in Sonchus oleraceus in a glasshouse experiment, and then evaluated the effects of temperature and precipitation variables on each of the traits.…”
Section: Methodsmentioning
confidence: 98%
“…Mature weed plants in each plot were identified, and the number of capitula were recorded to generate an estimate of the average number of capitula per plant in each plot: if fewer than five plants were found in a plot, the number of capitula on each was recorded, and if more than five plants were identified, five were randomly selected from the plot for capitula counts. These numbers were multiplied by the number of plants per plot from the earlier posttreatment weed counts and an estimated average of 170 seeds per capitula based on the literature (Mobli et al 2020;Ollivier et al 2020). Due to low weed densities in 2018 at RS2, an extra weed density assessment was completed before presowing herbicide treatments in 2019.…”
Section: Experimental Design and Samplingmentioning
confidence: 99%
“…More research is needed to determine the relative fitness advantages of admixed versus non-admixed genotypes of S. oleraceus in Australia over several generations (Cristescu, 2015). However, a recent study by Ollivier et al (2020) showed that S. oleraceus plants from S8). In other Asteraceae species that have become successful invaders, there is similar evidence of repeated introductions from different geographical areas (Eriksen et al, 2015;van Boheemen et al, 2017).…”
Section: Introductions From the Native Range And Admixturementioning
confidence: 99%
“…These human-mediated introductions are likely to have promoted admixture from multiple sources followed by recombination and selection for multiple traits in introduced Australian S. oleraceus plants (Ollivier et al, 2020).…”
Section: Introductions From the Native Range And Admixturementioning
confidence: 99%